An Investigation into BMP9-induced postnatal maturation of articular cartilage - MILES ANDERSON-WATTERS (2023)
Postnatal maturation is a process of articular cartilage development in which the tissue acquires biomechanical properties allowing lifelong cyclical loading in adults. During postnatal maturation cartilage undergoes structural and morphological changes, including the reorganisation of the collagen network from isotropic to one that is anisotropic, forming distinct zonal regions of collagen architecture and chondrocyte organisation. However, the mechanisms underlying the process of maturation are poorly understood. Currently there are no in vitro biological models of maturation, limiting study of this phenomenon to snapshots of histological, biochemical and biophysical changes. In this study we have shown that in situ culture of immature bovine cartilage explants with BMP9 induces changes in collagen structure and chondrocyte organisation recapitulating the zonal features of mature articular cartilage. We found BMP9 stimulates reorganisation of the collagen network causing the reorientation of mid and deep zone fibres perpendicular to the cartilage surface. Inhibition of matrix metalloproteinases (MMPs) via doxycycline prevented the changes observed in collagen alignment. Our results demonstrate that there is increased MMP3 expression and a reduction in tissue inhibitors of metalloproteinases-1 and -2 resulting in an increase in proteoglycan turnover and uptake of water. Of significant note were observations that show that cellular proliferation is involved in maturation, contrary to findings in mouse cartilage postnatal development, and immunological data showing that remodelling of collagen does not require enzymatic cleavage of pre-existing fibres. Whilst observations of BMP9 induced postnatal maturation in explants were variable, in vitro analysis using isolated chondrocytes grown as pellet cultures provided unequivocal evidence of the role of BMP9 in postnatal organisation of collagen fibrils in immature chondrocytes. In addition, pellet cultures show that mature chondrocytes have an intrinsic ability to recapitulate the mature cartilage collagen architecture, but even this is enhanced in the presence of BMP9. Therefore, we have developed useful models of postnatal maturation that have shone light on several important mechanisms that regulate the transition to maturity. We anticipate that our models of BMP9 induced postnatal maturation will provide the basis for further research into understanding the detailed mechanisms involved, guiding the development of more successful tissue engineering strategies.